PENGGUNAAN DANSEIGO OLEH TOKOH MORDRED DALAM ANIME FATE APOCRYPHA KARYA YUICHIRO HIGASHIDE - Edwin Adetama; Arza Aibonotika; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was conducted to find out what types of language are misused and what causes misuse or deviation of language use that can occur in the character Mordred in the anime Fate Apocrypha. The type of research used is qualitative and descriptive methods. The source of the data is taken from 25 episodes in the Fate Apocrypha anime. The method of data collection carried out is observation, listening, and recording. The results of this study show that abuse or deviation of language use by speakers who have different genders can be caused by several factors in accordance with Hymes' theory, namely SPEAKING that the place, situation, social status of participants, purpose of speech, form of speech, how the speech is conveyed, the means used, norms and types of speech can be the cause of abuse or deviation of language use can occur.Key words: Danseigo, Anime, Fate Apocrypha, Yuichiro Higashide